Nonenhancing Component of Clear Cell Renal Cell Carcinoma on Computed Tomography Correlates With Tumor Necrosis and Stage and Serves as a Size-Independent Prognostic Biomarker. Issue 4 (July 2019) - Ahmed, Firas S.; Akin, Oguz; Shaish, Hiram; Luk, Lyndon; Guo, Xiaotao; Yang, Hao; Zabor, Emily; Ostrovnaya, Irina; Hakimi, A. Ari; Zhao, Binsheng; Schwartz, Lawrence H.
Abstract : Objectives: This study aimed to quantify nonenhancing tumor (NT) component in clear cell renal cell carcinoma (ccRCC) and assess its association with histologically defined tumor necrosis, stage, and survival outcomes. Methods: Among 183 patients with ccRCC, multi-institutional changes in computed tomography attenuation of tumor voxels were used to quantify percent of NT. Associations of NT with histologic tumor necrosis and tumor stage/grade were tested using Wilcoxon signed rank test and with survival outcomes using Kaplan-Meier curves/Cox regression analysis. Results: Nonenhancing tumor was higher in ccRCC with tumor necrosis (11% vs 7%; P = 0.040) and higher pathological stage ( P = 0.042 and P < 0.001, respectively). Patients with greater NT had higher incidence of cancer recurrence after resection ( P < 0.001) and cancer-specific mortality ( P < 0.001). Conclusion: Nonenhancing tumor on preoperative computed tomographic scans in patients with ccRCC correlates with tumor necrosis and stage and may serve as an independent imaging prognostic biomarker for cancer recurrence and cancer-specific survival.